Magnon Torque Transferred into a Magnetic Insulator through an Antiferromagnetic Insulator - Zhiren Chen (MDPI AG, 2021)
Electrical spin-orbit torque (SOT) in magnetic insulators (MI) has been intensively studied due to its advantages in spin-orbitronic devices with ultralow energy consumption. However, the magnon torque in the MIs, which has the potential to further lower the energy consumption, still remains elusive. In this work, we demonstrate the efficient magnon torque transferred into an MI through an antiferromagnetic insulator. By fabricating a Pt/NiO/Tm<semantics>3</semantics>Fe<semantics>5</semantics>O<semantics>12</semantics> heterostructure with different NiO thicknesses, we have systematically investigated the evolution of the transferred magnon torque. We show that the magnon torque efficiency transferred through the NiO into the MI can retain a high value (∼50%), which is comparable to the previous report for the magnon torque transferred into the metallic magnet. Our study manifests the feasibility of realizing the pure magnon-based spin-orbitronic devices with ultralow energy consumption and high efficiency.